MERESPON GLOBALISASI DENGAN ALIANSI STRATEGIS : SUATU KEHARUSAN - Wahyuningsih Wahyuningsih (Media Riset Bisnis & Manajemen, 2005)
Aliances between organizations have become an increasingly popular method of development. Dynamic markets, coupled with the increasing costs of doing business, have resulted in a significant increase in the use of strategic alliances. Firms in many industries must develop new capabilities in many areas, ranging from tecnologically development to manufacturing process, from plant economies to marketing and distributin, and they must do so quickly. Developing such competitive capabilities with limited resources is the core of strategic alliances, which allow firms to recast their competitive strategies in response to głobalization.